(untitled) (Journal of Management and Social Sciences, 2022)
The internal security challenges troubling the peaceful coexistence of Nigeria in the 21st century derive from within Nigerians. This paper examines the effect of governance on security challenges in Nigeria between 2015 and 2019. The paper adopts content analysis to investigate the nexus between governance and the security challenges confronting Nigeria. The paper is anchored on Prebendalism and Frustration Aggression Theories to provide theoretical orientation for the paper. The paper concludes that corruption and inadequacies in internal security policies are the major factors behind the security challenges in Nigeria in the period under review. The paper recommends that government at all level should truly fight against corruption, poverty, nepotism, favouritism and unemployment. If the country is to regain its peaceful coexistence that is being gradually eroded.